A phenomenological study of the lived experiences of street vendors in Iloilo City. - Dellera, Patricia C
My study aimed to explore the lived experiences of street vendors in Iloilo. With Interpretative Phenomenological Analysis (IPA) as framework, I gathered data using semi-structured interviews among 6 street vendors within the province. The data collected are analyzed using the steps required by IPA. The results of the study showed that the lived experiences of street vendors can be grouped into 3 main themes, which are that of becoming a street vendor, confronting challenges of street vending, and relishing the benefits of street vending. The findings of my study will provide additional literature and new knowledge on the phenomenon of street vending, the experiences of street vendors, and IPA. The results of the study may be of value to policy makers, Local Government Units (LGUs), and Non-government Organizations (NGOs) as they have implications on the provision of programs that are beneficial for street vendors. Future studies may use different contexts, research methods, and data-gathering procedures to further investigate and capture the lived experiences of street vendors.